Les effets de raccommodement du récit de vie : l’exemple d’anciens appelés d’Algérie - Corinne Chaput-Le Bars (Recherches en Éducation)
War situations are extreme situation in which ordinary soldiers or civilian have been engaged in spite of themselves and for a significant number of them, these intense situations of violence leave trauma on medium or maybe long-term. They now have a name : PTSDs (Post-Traumatic Syndrom Disorders). Two models of management of this post-traumatic stress emerged, which are sometimes opposed, mistakenly : the immediate care and the cognitive way, more distanced, which focalized in a past that we do not forget. Life story is one of the privileged forms of introspection and the search of sense about what is inherently senseless. It can then be a tutor of resilience or, to use a concept that I explored, promote self-racommodement and between him/herself with others. However, among the wars which concerned France for the last hundred years, that of Algeria is probably one of those where the transmission was the most difficult and where, now, the urgency to be heard may be the most important. I collect four stories of former conscript wrote on their extreme experience forty to fifty years after completing their military service across the Mediterranean. These « computscripts » had been given to the Association for autobiography and autobiographical heritage (one of them was even published then) or kept in the family for a smaller spread for relatives. I have locked for the effects of racommodement and resilience made by these autobiographies.